2023
DOI: 10.1007/s00382-023-06934-0
|View full text |Cite
|
Sign up to set email alerts
|

The 2021 Atlantic Niño and Benguela Niño Events: external forcings and air–sea interactions

Serena Illig,
Marie-Lou Bachèlery

Abstract: This paper presents a comprehensive analysis of the extreme Atlantic and Benguela Niño events that occurred during the boreal spring–summer of 2021. We conducted sensitivity experiments with a regional ocean–atmosphere coupled model of the tropical Atlantic to investigate the phenology of these interannual events, unravel their triggering mechanisms, and quantify the contributions of local and remote processes. The results revealed that both the 2021 Atlantic and Benguela Niños were triggered by anomalous atmo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…At the same time, the shape of the coastline and regional bathymetry, which are critical for CTW propagation, play a key role in modifying the dynamics of temperature anomalies along the coast. Changes in river dynamics and coastline morphology can alter the interplay between CTWs and other oceanic processes 37 , further influencing the observed SST/SLA dynamics. These patterns persist across regions and months, highlighting the critical role of local processes, including CTWs, in shaping the intricate temperature anomalies observed in the GoG and the southeast Atlantic.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…At the same time, the shape of the coastline and regional bathymetry, which are critical for CTW propagation, play a key role in modifying the dynamics of temperature anomalies along the coast. Changes in river dynamics and coastline morphology can alter the interplay between CTWs and other oceanic processes 37 , further influencing the observed SST/SLA dynamics. These patterns persist across regions and months, highlighting the critical role of local processes, including CTWs, in shaping the intricate temperature anomalies observed in the GoG and the southeast Atlantic.…”
Section: Resultsmentioning
confidence: 99%
“…7 ). Illig and Bacherely 37 observed a long-term oceanic memory resulting from free-propagating downwelling equatorial waves forced before 2021. These waves warmed the slightly colder than normal surface layer near the equatorial waveguide during the first trimester of 2021, leading to neutral conditions by March 2021, just before the onset of an equatorial event.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that the high correlation between SST anomaly changes in the ABA and the Atl3 may be due to coastally trapped internal waves propagating from the ABA to the Atl3. Illig et al (2020) and Illig and Bachèlery (2024) have shown that when interannual wind-stress forcing is limited to the western-central equatorial Atlantic, Atlantic Niño events occur before coastal events, making it difficult to explain the fact that heat in the Atl3 comes from the south. However, if wind-stress anomalies are also present in the coastal region, the coastal warming occurs before the Atlantic Niño, providing a possible explanation for the result that heat in the Atl3 originates from the south.…”
Section: Discussionmentioning
confidence: 99%
“…6). Several authors (Walter, 1937;Boyd and Thomas, 1984;Boyd et al, 1987; During the Benguela Niño (Niña) events, an increase (decrease) in sea surface temperatures (SSTs) occurs in the eastern equatorial and south-east Atlantic Ocean due to the relaxation (intensification) of the trade winds (Rouault et al, 2007;Rosell-Melé et al, 2014;Illig and Bachèlery, 2024). The reduction in intensity of the trade winds during the Benguela Niño induces warmer SST in the equatorial Atlantic and the ingress of warm Angola water in the BUS (Hisard, 1980;Philander, 1990;Illig et al, 2004).…”
Section: Variations Of the Paleoceanographic Conditions During The Qu...mentioning
confidence: 99%